2016
DOI: 10.1073/pnas.1611193113
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic reaction of silver nitrate, silver nanoparticles, and methylene blue against bacteria

Abstract: In this paper we describe the antibacterial effect of methylene blue, MB, and silver nitrate reacting alone and in combination against five bacterial strains including Serratia marcescens and Escherichia coli bacteria. The data presented suggest that when the two components are combined and react together against bacteria, the effects can be up to three orders of magnitude greater than that of the sum of the two components reacting alone against bacteria. Analysis of the experimental data provides proof that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…For reagents, silver ions have target chemotoxicity toward bacteria other than biohosts and the integration of silver nanoparticles in the MPs@SiO2@Ag can reduce the nanotoxicity due to large particles sizes (>300 nm). [9a,17b] By combining the designed structures (nanoshells with surface roughness) and selected killing reagents (silver ions) of silver materials, we achieved long‐term bacteria inhibition for potential hospitals and daily use.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For reagents, silver ions have target chemotoxicity toward bacteria other than biohosts and the integration of silver nanoparticles in the MPs@SiO2@Ag can reduce the nanotoxicity due to large particles sizes (>300 nm). [9a,17b] By combining the designed structures (nanoshells with surface roughness) and selected killing reagents (silver ions) of silver materials, we achieved long‐term bacteria inhibition for potential hospitals and daily use.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel to detection, inhibition of bacteria is not only required in clinics, but is also a daily issue for health care . Notably, efficient inhibition of bacteria relies on engineered materials and should address the following aspects: 1) designed materials structures for bacteria surface adhesion and long‐term antibacterial effects; 2) selection and loading of antibacterial reagents to form hybrids; 3) inherent toxicological effects of nanomaterials toward the hosts; and 4) new perspectives toward the biological mechanism during antibacterial process . Most current efforts are focused on some of the above issues and few reports are on the design of one platform to tackle these aspects in all.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological action of silver nanoparticles relies upon the morphology and physicochemical properties of the nanoparticles, and in addition the particular qualities of microorganisms which are dealt with by silver nanoparticles [76]. One can recognize various elements influencing the antimicrobial action, for example, shape, size and zeta (ζ) potential of the metal particles which impact the surface properties of the particles and the stabilizer, the pH of the suspension, ionic quality contaminants and so forth [77].…”
Section: Factors Affecting the Antimicrobial Activity Of Silver Nanopmentioning
confidence: 99%
“…The advantages of PS‐based nMOFs make them promising for efficient APDT, while have not been reported yet. Moreover, it has been reported that the strong synergistic antimicrobial effect of silver nitrate and methylene blue were existed; however, the sustained high toxicity and small molecular characteristic restrict their further biomedical applications . Therefore, it is highly desirable to fabricate a biocompatible and controllable antimicrobial nanoplatform based on PS‐incorporated nMOFs to make full use of the synergistic effect of silver ions and ROS.…”
Section: Introductionmentioning
confidence: 99%